2007
DOI: 10.1016/s0929-6646(09)60231-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seroprevalence of Hepatitis B Virus and Hepatitis C Virus in Taiwan from a Large-scale Survey of Free Hepatitis Screening Participants

Abstract: This study estimated a 17.3% seroprevalence of HBV and a 4.4% seroprevalence of HCV in Taiwan. Significant geographic variations in the seroprevalence of HBV and HCV were found. These data suggest the importance of modifying programs for the prevention and treatment of chronic viral hepatitis in Taiwan to reflect its varying prevalence and epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
207
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(229 citation statements)
references
References 19 publications
16
207
6
Order By: Relevance
“…In Taiwan, HBV and HCV are endemic and are acquired via different modes of transmission. Most patients with CHB tend to acquire the infection early in life, usually perinatally, whereas many patients with CHC acquire the infection as young adults [10,11]. The comparison of the safety data from the clinical practice of Peg-IFN-based therapy in CHB and CHC provides a unique opportunity to investigate the effects of this treatment in a Taiwanese patient population with two distinct but related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Taiwan, HBV and HCV are endemic and are acquired via different modes of transmission. Most patients with CHB tend to acquire the infection early in life, usually perinatally, whereas many patients with CHC acquire the infection as young adults [10,11]. The comparison of the safety data from the clinical practice of Peg-IFN-based therapy in CHB and CHC provides a unique opportunity to investigate the effects of this treatment in a Taiwanese patient population with two distinct but related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, HBV and HCV infections are endemic and are the most important agents of chronic liver disease [10,11]. Whether the intensity and frequency of AEs are similar between Taiwanese patients with CHB and CHC who receive Peg-IFN-based therapy remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan is a hyper-endemic region for liver diseases such as cirrhosis and hepatocellular carcinoma (HCC), and infection with hepatitis B virus (HBV) and hepatitis C virus (HCV) are primary etiologic factors [1,2]. Before the launch of the universal childhood HBV vaccination policy in 1984, the prevalence rate of HBV infection in Taiwan was 15% to 20% [3].…”
Section: Introductionmentioning
confidence: 99%
“…Further, mortality due to fulminant hepatic failure and HCC also dramatically decreased following implementation of the vaccination program [7]. In a large-scale Taiwanese survey undertaken for evaluating HBV and HCV seroprevalence, increased HBsAg and anti-HCV seroprevalence rates (17.3% and 4.4%, respectively) were observed due to the inclusion of subjects born prior to the vaccination era [2]. Recent results from a literature review evaluating the burden of HCV in Asia confirmed HCV infection rates of 1.8% to 5.5% in Taiwan [8].…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan is an area hyper-endemic for chronic HBV/ HCV infection and HCC (Tsai et al, 2001(Tsai et al, , 2004IARC, 2004;Chen et al, 2007;Kee and Lu, 2011). Persistent hepatic inflammation is a hallmark of habitual BQ chewing (Sarma et al, 1992;Lin et al, 2008;Angadi and Rao, 2011) and/or chronic HBV/HCV infection (Bouchard and Navas-Martin, 2011;El-Serag, 2012).…”
Section: Introductionmentioning
confidence: 99%